Influence Presenteeism and Absenteeism Work Towards Commitment Work with Quality Work Employee as a Variable Intervening at the Representative Officeof Bank Indonesia Pematangsiantar - Viance Tawarta Sinaga; Sri Rahayu (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of Presenteeism and Absenteeism on Work Commitment, with Employee Work Quality as an intervening variable at the Bank Indonesia Representative Office in Pematangsiantar. The research approach used a quantitative method with Structural Equation Modeling (SEM) analysis techniques based on SmartPLS 3.0. The research sample consisted of all employees at the Bank Indonesia Representative Office in Pematangsiantar. The results indicate that Presenteeism and Absenteeism significantly influence Employee Work Commitment and Work Quality. Furthermore, Employee Work Quality has been shown to significantly influence Work Commitment. However, the results of the indirect effect test indicate that Employee Work Quality is unable to mediate the relationship between Presenteeism and Absenteeism on Work Commitment, thus the indirect effect is declared insignificant. This study implies that managing employee attendance and performance levels needs to be a critical focus to improve work quality and commitment within an organization.